Assessing ‘no evidence of disease activity’ status in patients with relapsing–remitting multiple sclerosis: a long-term follow-up - Zilli, Chiara; Scribani Rossi, Pietro; Di Stadio, Arianna; Fratino, Mariangela; Giuliani, Giada; Annecca, Rosanna; Russo, Gaetano; Di Piero, Vittorio; Altieri, Marta (Frontiers in Neurology, 2023)
Introduction Multiple Sclerosis (MS) is a chronic inflammatory demyelinating disease of the CNS with an autoimmune pathogenesis. Over the years, numerous disease-modifying therapies (DMTs) have proven effective in disease control; to date, there is a need to identify a personalized treatment effective in ensuring disease-free status or no evidence of disease activity (NEDA). Objective identify clinical, demographic and treatment approach characteristics that affect the maintenance of NEDA-3 and the occurrence of clinical relapses during a 6-years follow-up. Materials and method a retrospective study was conducted on a cohort of MS patients followed up with six-year period. All participants were treated with first- or second-line MS drugs. Clinical relapse, NEDA-3 at 6 years and sustained EDSS were assessed as disease activity outcomes. Patients with follow-up of less than 6 years and insufficient clinical and radiological data were excluded from the study. Results Two-hundred-eighty naive patients (mean age was 49.8 years, SD ± 11.35 years, 23–76, F/M 182/98), with MS were followed up for 6 years. The mean age at diagnosis was 34.3 years (SD ±11.5, 14–62 years), the mean EDSS score at the onset was 1.9 (±1.3), 76.8% of patients had an EDSS below or equal to 2.5 at diagnosis. In the cohort 37 (13.2%) directly received second-line treatment, 243 (86.8%) received first-line drugs. The analysis showed that second-line treatment from beginning had a protective effect for the achievement of NEDA-3 (p = 0.029), on the prevention of clinical relapse (p = 0.018) and on number of relapses (p = 0.010); this finding was confirmed by logistic regression analysis (p = 0.04) and Kaplan–Meier analysis (p = 0.034). Conclusion The results of this study demonstrate the efficacy of targeted and early intervention so as to act in the right time window, ensuring a favorable outcome in both clinical and radiological terms; this could be decisive in reducing clinical relapse, disease progression and related disability. Therefore, prescribing highly effective drug in the early stages of the disease represents a leading strategy with the most favorable cost–benefit ratio.